The impact of executive compensation equity on corporate performance - TIAN, LUWEN (2019)
This study investigates the influence of executive compensation equity on enterprise performance. Models are tested on the data of China’s listed companies for the period 2014-2018. The study reveals that the internal executive compensation gap has an inverted u-shaped relationship with enterprise performance and external equity of executive compensation has a significant positive relationship with enterprise performance. Regarding the equity nature, the external compensation equity of executives in nonstate-owned enterprises (non-SOEs) has more impact on enterprise performance than in state-owned enterprises (SOEs). Meanwhile, compared with SOEs, the internal compensation gap in non-SOEs is more closely related to their performance. This study contributes to comprehensively studying how executive compensation equity affects corporate performance from the perspective of internal salary gap and external compensation equity, and to make a comparison between SOEs and non-SOEs according to China's unique background, thus contributing to the improvement of firm performance.